P2P lending approval and sectors segmentation: investigating the Malaysia key factors / Nur’Asyiqin Ramdhan ... [et al.] - Ramdhan, Nur’Asyiqin; Bujang, Imbarine; Muhamat, Amirul Afif; Hendrawaty, Erni; Hoong, Tay Bee (Universiti Teknologi MARA Selangor, 2024)
The purpose of this research is to determine the long- and short-run factors influencing the probability of obtaining loan under the peer-topeer (P2P) lending platform with the segmentation of wholesale and trade, manufacturing, and agriculture sectors. As the FinTech lending is a popular tool for business financing alternative among the Micro, Small Medium Enterprises (MSMEs), the effect of information asymmetry may be varied from one industry to another. The study was conducted using data provided by Securities Commissions and Central Bank of Malaysian samples and employed the Autoregressive Distributed Lag (ARDL) approach. The results indicate that the interest rate on the platform has an insignificant impact on the success of P2P lending over time. On the other hand, factors such as loan tenure, investment size, Base Lending Rate (BLR), and inflation exhibit a significant influence in both the short and long term, depending on the segmentation of industrial sectors. This study is among the pioneering works that delve into P2P lending in Malaysia, considering that the concept has only been implemented since 2017. These research findings can be viewed as valuable insights for industrial borrowers, lenders, and platforms when engaging in economic activities through P2P lending, particularly in the Malaysian context.